An Etnography of Communication Study on the Merantau Cultural Praktice among the Minangkabau Student Association in Surabaya - Safrina Ika Desinta; Syafrida Nurrachmi Febriyanti (Interaction Communication Studies Journal, 2026)
Merantau is a longstanding cultural tradition of the Minangkabau community that serves as a process of fostering independence, maturity, and personal development. In contemporary society, this tradition has undergone a shift in meaning, particularly among students who migrate to pursue higher education. Understanding how these students communicate and negotiate their cultural identity is important for multicultural student organizations and higher education institutions in creating inclusive environments that support intercultural adaptation while preserving cultural diversity. This study aims to describe the communication practices of Minangkabau students in interpreting the merantau tradition within the Minangkabau Student Association (IMAMI) in Surabaya, analyze the transformation of its cultural meaning, and explain how communication practices facilitate cultural adaptation while preserving Minangkabau cultural identity. This study employed a qualitative approach using communication ethnography. The participants were Minangkabau students who were active members of IMAMI Surabaya, and the communication practices were analyzed using Dell Hymes’ SPEAKING framework. The findings reveal that communication practices function not only as a means of information exchange but also as a medium for transmitting cultural values, strengthening solidarity, and reinforcing cultural identity. The meaning of merantau has shifted from primarily seeking economic livelihood to pursuing higher education, developing personal capacities, expanding social networks, and cultivating independence and responsibility. Furthermore, students adapt their communication styles and language use to the multicultural environment of Surabaya without abandoning their cultural values. The practice of maota lamak also plays a significant role in preserving Minangkabau cultural identity by facilitating advice-sharing, exchanging experiences, strengthening kinship, and transmitting traditional values. This study concludes that the communication practices of Minangkabau students in IMAMI Surabaya demonstrate successful cultural adaptation while maintaining their cultural identity.